Oxidative Stress Level as a Predictor of Anastomotic Leakage after Rectal Surgery - Jiajun Luo; Hongxue Wu; Yu Yang; Yue Jiang; Jingwen Yuan; Qiang Tong (Mediators of Inflammation)
Background. Early diagnosis of anastomotic leakage (AL) after rectal surgery can reduce the adverse effects of AL, thereby reducing morbidity and mortality. Currently, there are no accepted indicators or effective scoring systems that can clearly identify patients at risk of anastomotic leakage. Methods. A prospective study with assessment of the diagnostic accuracy of oxidative stress level (CAT, SOD, MDA) in serum and drain fluid compared to white blood cell count (WBC), C-reactive protein (CRP), and neutrophil percentage (NEUT) in prediction of AL in patients undergoing elective rectal surgery with anastomosis. Results. Most of the oxidative stress indicators we detected are of considerable significance in the diagnosis of anastomotic leakage. The level of MDA on postoperative day (POD)3 (areas under the curve (AUC): 0.831) and POD5 (AUC: 0.837) in the serum and on POD3 (AUC: 0.845) in the drain fluid showed the same excellent diagnostic accuracy as the level of CRP on the POD3 (AUC: 0.847) and POD5 (AUC: 0.896). Conclusions. The overall level of oxidative stress in serum and drain fluid is a reliable indicator for the early diagnosis of anastomotic leakage after rectal surgery. More specifically, among the redox indicators analyzed, MDA has almost the same predictive value as CRP, which provides another useful biomarker for the early diagnosis of anastomotic leakage.